Assessment: How to Survive It and How to Benefit from It - Robert Blumenthal (Academic Chairpersons Conference Proceedings, 2015)
In this roundtable, we will discuss how to meet the various challenges associated with the assessment of student learning outcomes and how to achieve faculty buy-in, and we will discuss some stragegies for constructing and implementing an assessment plan.
Keywords: student learning outcomes; assessment; accreditation; implementation; faculty